The Impact of Infrastructure Development and the Role of Community Leaders on the Number of Visits and the Image of Spinsur Tourism in the Lake Toba Region, North Sumatra with the Partial Least Square Method - Riko Fridolend Sianturi; Lasma Ria Tampubolon; Ferdinand Napitupulu (LPPM STIE EKA PRASETYA, 2022)
This study aims to analyze and examine the Impact of Infrastructure Development and the Role of Community Leaders on the Number of Visits and the Image of Spinsur Tourism in the Lake Toba region, North Sumatra. The research location was taken at Sipinsur Tourism Object, which is located in Paranginan District, Humbang Hasundutan Regency. The sample size used is 100 people. The sampling technique used is simple random sampling. The research was conducted from 2019 to 2020. There are two data collected, namely primary data in the form of questionnaires and secondary data obtained through books, literature and other sources. The research method uses Partial Least Square (PLS). The results showed that infrastructure development had no positive and insignificant effect on the number of visits, the role of community leaders had a positive and significant effect on the number of visits, and infrastructure development had no positive and insignificant effect on tourism image. The role of community leaders had a positive and significant effect on tourism image. The community has a positive and significant effect on the image of tourism, the role of community leaders has a positive and significant effect on the image of tourism, infrastructure development has no positive and insignificant effect on the image of tourism through the number of visits and the role of community leaders has a positive and significant effect on the image of tourism through the number of visits.